Mortality involving New Psychoactive Substances across Europe, 2016-2017 - Hugo López-Pelayo; Julian Vicente; Ana Gallegos; Andrew McAuley; Yalçın Büyük; Martin White; Isabelle Giraudon (Elsevier, 2021)
Background-Aims: New psychoactive substances (NPS) are new narcotic or psychotropic drugs that are not controlled by the drug conventions of the United Nations. In the last 10 years, numerous NPS have been identified in Europe but there is no comprehensive overview of mortality related to them. This study aims to estimate the mortality related to NPS in Europe in 2016 and 2017. Methods: The number of drug-related deaths (DRD) 2016-2017 was retrieved from a) the annual national reports of European Monitoring Centre for Drugs and Drug Addiction (EMCDDA) countries (Statistical Bulletin (2018/2019) and 'Harms and harm reduction workbooks' (2017/2018)) and b) EMCDDA Risk Assessment Reports of the EU Early Warning System on several specific NPS (2017-2018). Population data was retrieved from Eurostat (2016/2017). Incidence of DRD and of DRD involving at least one NPS was calculated. Findings: Of all DRD recorded in Europe, 11.7% in 2016 and 18.1% in 2017 involved at least one NPS (NPS-DRD), from 2.7 to 4.9 deaths per million of 15 to 64-year-old inhabitants. Between 2016 and 2017, a significant increase was observed (30%, odds ratio 1.33, CI95% 1.26-1.45, p < 0.0001) and in particular, DRD involving novel benzodiazepines, novel opioids and synthetic cannabinoids (p < 0.0001). In 2016 and2017, 72.8% and 76.8% of cases were concentrated in the UK and Turkey (combined), related mainly to Etizolam and synthetic cannabinoids respectively. Interpretation: In 2017, one in six drug-related deaths in Europe involved NPS, and the proportion and numbers increased from 2016 levels, although three out of four cases were concentrated in only two countries and a few substances. To fully understand the public health implications of NPS, further monitoring on NPS-DRD and their distribution in Europe is needed.